Synthesis of enantiomerically pure N-(2,3-dihydroxypropyl)arylamides via oxidative esterification - Akula Raghunadh (Beilstein Journal of Organic Chemistry, 2013)
A highly efficient synthesis of enantiomerically pure (S) and (R)-isomers of N-(2,3-dihydroxypropyl)arylamides has been developed with good overall yields in a two step process. The key step involves the ring opening of the chiral epoxide with a nitrogen heterocyclic carbene (NHC) and further rearrangement to chiral N-(2,3-dihydroxypropyl)arylamides in high yields and enantioselectivity. During the reaction, no erosion in chiral purity was observed.